Some properties and expressions of solutions for a class of nonlinear difference equation - Elabbasy E.M.; El-Metwally H.; Elsayed E.M. (Utilitas Mathematica, 2012)
In this paper we study some properties of solutions of difference equation x n+1 = ax n-2 +bx n-2x n-3/cx n + dx n-3, n=0, 1,..., where the initial conditions x -3, x -2, x -1, x o are arbitrary positive real numbers and a,b,c,d are constants. Also, we give the expressions of solutions for some special cases of this equation.